Europe unbound : enlarging and reshaping the boundaries of the European Union - Zielonka, Jan, 1955- (London ; New York : Routledge, 2003)
This book provides an analysis of the enlargement of the European Union. Drawing upon such diverse fields as history, sociology, political science and international relations.
Book Cover; Title; Contents; List of tables; List of contributors; Preface; List of abbreviations; Introduction: Boundary making by the European Union; Does Europe need a frontier?: from territorial to redistributive community; Fixed borders or moving borderlands?: a new type of border for a new type of entity; Facing the 'desert of Tartars': the Eastern border of Europe; Where does Europe end?: dilemmas of inclusion and exclusion; The geopolitical implications of enlargement; Ethnic minorities and long-term implications of EU enlargement.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: National security -- European Union countries; European Union countries -- Politics and government; European Union countries -- Emigration and immigration; European Union countries -- Boundaries; European Union countries -- Economic integration; Europe -- Economic integration; Pays de l'Union européenne -- Émigration et immigration; Europe -- Intégration économique.; LAW -- International; Boundaries; Emigration and immigration; International economic integration; National security; Politics and government; Europe; European Union countries; European Union; European integration; Migration; Ethnic minorities; Borders; Community law